A proteomic analysis unravels novel CORVET and HOPS proteins involved in Toxoplasma gondii secretory organelles biogenesis. (8th July 2018) - Morlon‐Guyot, Juliette; El Hajj, Hiba; Martin, Kevin; Fois, Adrien; Carrillo, Amandine; Berry, Laurence; Burchmore, Richard; Meissner, Markus; Lebrun, Maryse; Daher, Wassim
Abstract: Apicomplexans use the endolysosomal system for the biogenesis of their secretory organelles, namely, micronemes, rhoptries, and dense granules. In Toxoplasma gondii, our previous in silico search identified the HOPS tethering but not the CORVET complex and demonstrated a role of Vps11 (a common component for both complexes) in its secretory organelle biogenesis. Herein, we performed Vps11‐GFP‐Trap pull‐down assays and identified by proteomic analysis, not only the CORVET‐specific subunit Vps8 but also a BEACH domain‐containing protein (BDCP) conserved in eukaryotes. We show that knocking‐down Vps8 affects targeting of dense granule proteins, transport of rhoptry proteins, and the localization of the cathepsin L protease vacuolar compartment marker. Only a subset of micronemal proteins are affected by the absence of Vps8, shedding light on at least two trafficking pathways involved in microneme maturation. Knocking‐down BDCP revealed a restricted and particular role of this protein in rhoptry and vacuolar compartment biogenesis. Moreover, depletion of BDCP or Vps8 abolishes parasite virulence in vivo. This study identified BDCP as a novel CORVET/HOPS‐associated protein, playing specific roles and acting in concert during secretory organelle biogenesis, an essential process for host cell infection. Our results open the hypothesis for a role of BDCP in the vesicular trafficking towards lysosome‐related organelles in mammals and yeast.